Sacubitril/Valsartan in heart failure with reduced ejection fraction: clinical and echocardiographic insights from a real world population. (14th October 2021) - Valli, F; Bursi, F; Santangelo, G; Toriello, F; Rusconi, I; Mondellini, G; Vella, A.M; Faggiano, A; Persampieri, S; Carugo, S; Guazzi, M
Abstract: Background: Following the PARADIGM trial, some studies have identified cardiac remodeling as major background for hard end point benefits of Sacubitril/Valsartan (S/V), but few adopted a well described definition in the literature. Purpose: We aimed at a comprehensive evaluation of the effects of S/V on echo-derived measures of cardiac remodeling along with clinical and laboratory data over a medium-term follow-up pointing to a real-world HFrEF population. Methods: This is a prospective observational study of HFrEF patients on optimal medical therapy (OMT) initiated with S/V at Heart Failure Clinic of our institute (January 2017-January 2020). In 62 HFrEF, echocardiographic, laboratory and clinical data were collected at baseline and over 10 (Q1-Q3 8–13) months after S/V initiation. Mean age was 68±12 years, 79% men. Left ventricular reverse remodeling (LVRR) was defined as: 1) an absolute increase in LVEF ≥10 points or a LVEF ≥50% at follow-up and 2) a relative decrease in indexed left ventricular end-diastolic diameter of at least 10% or an indexed left ventricular end-diastolic diameter ≤33 mm/m 2 . Results: Compared to baseline, S/V promoted a significant improvement of LV ejection fraction (LVEF, from 30% to 37%; p<0, 0001) with an absolute median increase in LVEF of 8 points. Parallel significant reductions in left ventricular and atrial volumes, lower mitral regurgitation degree and a better diastolic dysfunction along with clinical improvement (NYHA class and NT-proBNP values) were observed at follow up. sPAP (systolic Pulmonary Arterial Pressure) was significantly decreased at follow-up evaluation (37 mmHg vs 31 mmHg p=0, 005) (Table 1). Overall, LVRR as defined above was observed in 30% of patients. Younger age (64 vs 74 years, p=0, 007), a shorter duration of the disease (7 vs 23 months, p=0, 009), and non ischaemic etiology (79% vs 33% p=0, 003), along with a smaller baseline LAESVi (Left Atrial End Systolic Volume, 41 vs 48 ml/m 2 p=0, 012) were more common in patients with LVRR. sPAP and Right Ventricular (RV) function estimated by tricuspid annular plane systolic excursion (TAPSE) were significantly better in LVRR patients along with TAPSE/sPAP ratio (Table 2). Conclusions: Our data point to a remarkable medium-term reverse remodeling effect by S/V in HFrEF. Findings reinforce the concept that the main benefits of S/V on hard end-points are mediated by its cardiac-related effects. Both a left and right reverse remodeling occur in HFrEF patients who start S/V in the most adaptable phase of the disease supporting an early administration. Funding Acknowledgement: Type of funding sources: None.